Case report: CMV retinitis following local and systemic immunosuppression - Menke, Bryant A.; Wagner, William; Song, Helen; Thomas, William; Almeida, Natalia E. Castillo; Conrady, Christopher D.; Yeh, Steven (Frontiers in Ophthalmology, 2024)
We report the case of a 71-year-old man who presented 2 years following renal transplantation with diffuse, unilateral cytomegalovirus retinitis five weeks after receiving an intravitreal dexamethasone implant device for the management of central retinal vein occlusion. Examination of the left eye showed diffuse retinal hemorrhages, attenuated and tortuous retinal vessels, and superior retinal whitening. The patient was successfully treated with serial intravitreal foscarnet injections and oral valganciclovir with disease regression observed by 12 weeks after presentation. The patient’s visual acuity and examination remained stable at 9-months follow-up.